Analysis of Hydroquinone in Face Whitening Cream Circulating in Pinrang Regency - Mustafa, Diyan Nurkhalisah; Aminah, Aminah; Widiastuti, Harti (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
DIYAN NURKHALISAH M. Analysis of Hydroquinone in Face Whitening Cream Circulating in Pinrang Regency. (Supervised by Harti Widiastuti and Aminah). Whitening cream is a cosmetic preparation consisting of a mixture of chemicals and other ingredients that aims to whiten or fade black spots on the skin. Many people use whitening creams because they are sold freely. However, not all whitening creams that are sold freely are safe to use because they contain dangerous ingredients, such as hydroquinone. The purpose of this study was to analyze the hydroquinone compound in whitening cream circulating in Pinrang Regency and to find out how much hydroquinone it contained. Qualitative analysis of the four samples using the Thin Layer Chromatography (TLC) method positively contained hydroquinone which was indicated by the Rf values ​​of the samples and standard standards being the same and the appearance of purple spots which were detected under UV light of 254 nm. Quantitative analysis on four samples using the High Performance Liquid Chromatography (HPLC) method with a flow rate of 1 ml/minute, the mobile phase was methanol:aquabidestilata (55:45), the stationary phase was column C-18, the retention times of the sample and standard were obtained at the same value. namely 1.5 and 1.6 indicating that the sample contains hydroquinone. The linear regression equation y = 39.549x – 283.31 with a correlation coefficient of 0.998. The hydroquinone levels obtained were code A whitening cream of 2.5%; whitening cream B 2.8%; whitening cream C 2.45%; and whitening cream D by 0.9%.